A New Report of Parasa lepida Cramer (Lepidoptera : Limacodidae) and Trypanophora semihyalina Kollar (Lepid. : Zygaenldae) as Pests of Gmelina arborea - Meshram, P. B.; Garg, V. V. (Indian Forester, 2000)
No abstract